2016
DOI: 10.1002/bmc.3723
|View full text |Cite
|
Sign up to set email alerts
|

Rapid screening and identification of lycodine‐type alkaloids in Lycopodiaceae and Huperziaceae plants by ultra‐performance liquid chromatography coupled with quadrupole time‐of‐flight mass spectrometry

Abstract: Lycodine-type alkaloids have gained significant interest owing to their unique skeletal characteristics and acetylcholinesterase activity. This study established a rapid and reliable method using ultra-performance liquid chromatography coupled with electrospray ionization quadrupole time-of-flight tandem mass spectrometry (UPLC-ESI-Q/TOF-MS/MS) for comprehensive characterization of lycodine-type alkaloids for the first time. The lycodine-type alkaloids were detected successfully from Lycopodiastrum casuarinoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…Whereas, compound 2 , at 3.49 min, could be determined as huperzine B by comparing its precursor ion [M + H] + m/z 257 and MS 2 fragments at [M + H-NH 3 ] + m/z 240, [M + H-C 2 H 5 NH 2 ] + m/z 212, [M + H-C 3 H 7 NH 2 ] + m/z 198, and [M + H-C 4 H 9 NH 2 ] + m/z 184 to those in the literature data (Wu and Gu 2006 ; Shan et al. 2016 ). MS spectrum of compound 6 (retention time of 4.76 min) exhibited the molecular ion [M + H] + at m/z 279, together with MS 2 fragments at [M + H-CH 3 ] + m/z 264 and [M + H-CH 3 NH 2 -CH 3 -C 3 H 5 NO] + m/z 162.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…Whereas, compound 2 , at 3.49 min, could be determined as huperzine B by comparing its precursor ion [M + H] + m/z 257 and MS 2 fragments at [M + H-NH 3 ] + m/z 240, [M + H-C 2 H 5 NH 2 ] + m/z 212, [M + H-C 3 H 7 NH 2 ] + m/z 198, and [M + H-C 4 H 9 NH 2 ] + m/z 184 to those in the literature data (Wu and Gu 2006 ; Shan et al. 2016 ). MS spectrum of compound 6 (retention time of 4.76 min) exhibited the molecular ion [M + H] + at m/z 279, together with MS 2 fragments at [M + H-CH 3 ] + m/z 264 and [M + H-CH 3 NH 2 -CH 3 -C 3 H 5 NO] + m/z 162.…”
Section: Resultssupporting
confidence: 65%
“…Huperzine A (compound 3 ), the major phytochemical in H. serrata , could be identified at 3.89 min on the chromatogram due to the highest peak intensity and the precursor ion [M + H] + m/z 243 as well as the specific fragments, [M + H-NH 3 ] + m/z 226, [M + H-CH 3 -NH 3 ] + m/z 211, and [M + H-C 2 H 5 -NH 3 ] + m/z 197 (Wu and Gu 2006 ; Shan et al. 2016 ). Whereas, compound 2 , at 3.49 min, could be determined as huperzine B by comparing its precursor ion [M + H] + m/z 257 and MS 2 fragments at [M + H-NH 3 ] + m/z 240, [M + H-C 2 H 5 NH 2 ] + m/z 212, [M + H-C 3 H 7 NH 2 ] + m/z 198, and [M + H-C 4 H 9 NH 2 ] + m/z 184 to those in the literature data (Wu and Gu 2006 ; Shan et al.…”
Section: Resultsmentioning
confidence: 99%
“…However, the lycopodine-type alkaloids lack diagnostic fragments at collision energy of 35 eV and lower, and their identification relies on isolated pure standards. It has been reported that lycopodane-type alkaloids with saturated ring structures, such as lycopodine, selagoline and serratidine in H. selago (Staerk et al, 2004), are devoid of MS fragments at commonly used collision energy levels around 30-35 eV, and that only a few fragments could be expected to occur at a higher collision energy over 40 eV (Shan et al, 2016). Whether high collision energy levels (> 40 eV) could generate characteristic fragment ions for lycopodane-type LAs remains unexplored.…”
Section: Lc-ms Alkaloid Fingerprintingmentioning
confidence: 99%
“…Several analytical methods have been used to detect these lycorine‐type alkaloids including thin‐layer chromatography (TLC), capillary electrophoresis (CE), high performance liquid chromatography (HPLC), liquid chromatography‐tandem mass spectrometry (LC‐MS/MS) and gas chromatography‐mass spectrometry (GC‐MS) …”
Section: Introductionmentioning
confidence: 99%